Engineered multifunctional nanoparticles for enhanced radiation therapy: three-in-one approach for cancer treatment - Tejaswini Appidi; Debarghya China; George-Răzvan Ștefan; Michele Moreau; Serena Mao; Esteban Velarde; Ngeh Toyang; Henry Lowe; Aravind Kumar Rengan; Kai Ding; Wilfred Ngwa (Molecular Cancer)
Abstract Clinical cancer treatment modalities include radiation as one of the first-line therapies used for treating almost two-thirds of cancer patients. Combinational therapy for cancer is becoming extremely popular, with multiple therapies and their pharmacological effects expected to provide a synergistic outcome. The nanotechnology-based combinational therapeutic approach is emerging as a more effective strategy, for its advantages include simultaneous loading of multiple drugs, on-demand drug delivery controlled by external or internal stimulus, targeting a particular site, and the potential to combine physical treatment modalities (like radiation, thermal therapies, etc.) with chemical interventions (like chemotherapy, immunotherapy, etc.). We report a combination of radiotherapy and chemotherapy mediated by a multifunctional lipo-polymeric hybrid nanosystem coated with gold, demonstrating the three different functionalities using a single nanosystem: a) radio sensitization, b) radiation-triggered delivery of drugs, and c) application as an X-ray/CT contrast agent. The lipo-polymeric hybrid nanoparticles, synthesized using a modified hydrogel isolation method, were loaded with a natural plant-derived anti-cancer agent “Caflanone.” These nanoparticles were further subjected to in-situ reduction for a surface coating of gold, which provided enhanced radiosensitivity, radiation triggered drug delivery and X-ray/CT imaging. This approach using a multifunctional nanosystem leverages the biocompatibility of the lipo-polymeric hybrid system for the loading of drugs, precise spatiotemporal controllability of radiation for drug release, and the cytotoxicity of the plant-derived anti-cancer agent “Caflanone.” A significant therapeutic efficacy in vitro against breast cancer (p = 0.0002), pancreatic cancer (p < 0.0001), and glioblastoma (p < 0.0001) was demonstrated with the combinational approach. The application of the nanosystem as an X-ray/CT contrast agent has been shown in vivo in tumor-bearing mice and the safety profile and histopathology evaluated in healthy mice showed no adverse effects. A significant increase (p = 0.01) in the survival of breast tumor-bearing mice treated with a combinational approach was also demonstrated. The engineered multifunctional nanoparticles enhanced the radiation therapy and triggered the drug release at the tumor site, triggering the action of encapsulated chemotherapeutic agents while providing image guidance.